Управління розвитком кадрового потенціалу на підприємстві сільськогосподарського машинобудування - Лашкул, Ольга Олексіївна; Lashkul, Olha (ЦНТУ, 2024)
Кваліфікаційна робота присвячена управлінню розвитком кадрового потенціалу на підприємстві сільськогосподарського машинобудування. Досліджено теоретичні та практичні аспекти управління кадровим потенціалом з урахуванням сучасних економічних викликів. На основі результатів аналізу розроблено програму розвитку кадрового потенціалу, що включає рекомендації щодо оптимізації структури персоналу, підвищення кваліфікації працівників та впровадження аутсорсингових послуг для зниження витрат на навчання. The qualification work is devoted to the management of the development of personnel potential at the enterprise of agricultural engineering. The theoretical and practical aspects of personnel management are studied, taking into account modern economic challenges. Based on the results of the analysis, a personnel development program was developed, which includes recommendations for optimizing the personnel structure, improving the qualifications of employees, and introducing outsourcing services to reduce training costs.
Management of human resource potential development at the enterprises of agricultural machinery
Keywords: кадровий потенціал; сільськогосподарське машинобудування; розвиток персоналу; personnel potential; agricultural engineering; personnel development